Respuesta :

Start by setting up your two sets of parenthses.

Inside, we have the terms that compose each binomial.

Since x² breaks down into x · x, we use an x in each binomial.

The second term is the factors of -12 that add to the coefficient

of the middle term but what is the coefficient of the middle term?

If there is nothing written there, it's understood to be 1.

So factors of -12 that add to -1 are 4 and -4.

So we have (x + 4)(x - 3) which is our answer.

sand75

Answer:

x = 4 , x = -3

Step-by-step explanation:

x^2 - x - 12 = ( x - 4) ( x + 3)

x - 4 = 0 or x + 3 = 0

x = 4 or x = -3